Parenteral Nutrition with Oliclinomel N8-800 in Patients with Hypercatabolism during Extended Abdominal Surgery - V. A. Zyryanov; V. V. Stets; A. E. Shestopalov; G. M. Klimova; M. D. Lyubimov; N. G. Panova (Общая реаниматология, 2014)
Objective: to determine the efficiency of postoperative 3-in-1 parenteral nutrition with Oliclinomel N8-800 in correcting protein-energy malnutrition in patients undergoing extended surgical interventions into the abdominal organs. Subjects and methods. Forty-one patients with gastric and pancreatic neoplasms treated in the intensive care unit, N. N. Burdenko Main Military Clinical Hospital, in January to October 2013 were examined. All the patients were males. The mean age was 63.5±11.87 years. The study design: a prospective controlled randomized trial. Group 1 (a comparison group) entered 21 patients. Conventional parenteral nutrition regimens with Oliclinomel N7-1000E 2000 ml were used on postoperative day 2. The intestine was lavaged with a glucose-electrolyte solution within the first postoperative hours. The glucose-electrolyte solution and standard enteral formula were intraintestinally administered as the absorptive and digestive functions of the small bowel recovered. On postoperative days 7 and 8, the parenteral nutrition was stopped and completely switched to enteral feeding. The dissimilarity of Group 2 (a study group) (n=20) was that it received parenteral nutrition with Oliclinomel N8-800 2000 ml.Results. Complete parenteral nutrition, then mixed parenteral-enteral nutrition stabilized protein metabolic parameters in the patients of both groups in a unilateral fashion, but more promptly in Group 2 than in Group 1. The nutritional support program in Group 2 caused significantly less reduction in the body' cellular weight than in Group 2 in the first and entire period of the follow-up, which appears to be related to the administration of large amounts of nitrogen.Conclusion. The results suggest that the use of Oliclinomel N8-800 for parenteral nutrition adequately corrects postaggressive nitrogen deficiency, promotes the normalization of protein and carbohydrate metabolism and a positive nitrogen balance and the resolution of hypermetabolism/hypercatabolism after extended abdominal surgery.